The law of declaratory judgments - Sarna, Lazar (Thomson Reuters Canada Limited, 2016)
"[This book is a] review and study of declaratory judgments in Canada, a unique reference and guide to what declaratory judgments are, and when and how they can and should be used. The analysis of the subject includes reference to historical origins, procedural requirements, jurisdictional framework and application of the declaratory judgment in the determination of issues in constitutional, administrative, municipal, labour, contractual, and estate law. Along with an overview of the Canadian law, the author gives special attention to the experience of Quebec courts in the matter of declaratory relief. In addition to analyses and discussions of the substantive law, The Law of Declaratory Judgments, Fourth Edition also addresses the practical aspects of the law through provisions of precedents."-- Provided by publisher.